2011
DOI: 10.2116/analsci.27.1065
|View full text |Cite
|
Sign up to set email alerts
|

Sensitive Electrochemical Detection of the Hydroxyl Radical Using Enzyme-catalyzed Redox Cycling

Abstract: Enzyme-catalyzed signal amplification was introduced to the electrochemical detection of the OH radical. In the presence of phenol as a trapping agent, glucose as a substrate, and pyrroloquinoline quinone-containing glucose dehydrogenase (PQQ-GDH) as a catalyst, the current signal for the trapping adducts (catechol and hydroquinone) produced by the hydroxylation of phenol could be amplified and detected sensitively. The limit of detection (S/N = 3) for catechol was 8 nM. The trapping efficiency of phenol was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 14 publications
1
6
1
Order By: Relevance
“…In a similar manner, the TE value of 5.4% was obtained for hemoglobin. These TE values are much higher than that in our previous work, 0.06% [23], obtained for the Fenton reaction with Fe(II)-EDTA and H 2 O 2 at 25°C. This is probably due to the difference of the temperature and the Å OH-generating activity of Fe.…”
Section: å Oh Generation Induced By Xanthine-xo Systemcontrasting
confidence: 74%
See 2 more Smart Citations
“…In a similar manner, the TE value of 5.4% was obtained for hemoglobin. These TE values are much higher than that in our previous work, 0.06% [23], obtained for the Fenton reaction with Fe(II)-EDTA and H 2 O 2 at 25°C. This is probably due to the difference of the temperature and the Å OH-generating activity of Fe.…”
Section: å Oh Generation Induced By Xanthine-xo Systemcontrasting
confidence: 74%
“…In our previous study, we used phenol as a trapping agent, and the major hydroxylated adduct was catechol [23]. The applied potential for the detection of catechol was 0.28 V, which was positive enough to oxidize urate; thus, this method could not be employed for the xanthine-XO system.…”
Section: Amperometric Detection Of Hydroxylated Adductsmentioning
confidence: 99%
See 1 more Smart Citation
“…2). In our previous study, 14 the limiting current of Cat was more clearly observed when PQQ-GDH was dissolved in the test solution. The broader wave of Cat in the present study may be due to electrode fouling by the high concentration of PQQ-GDH immobilized on the surface of the electrode.…”
Section: Enzyme-catalyzed Signal Amplificationmentioning
confidence: 74%
“…In our recent study, enzyme-catalyzed signal amplification was introduced to the amperometric detection of the hydroxyl radical. 14,15 In the presence of an aromatic trapping agent, pyrroloquinoline quinone-dependent glucose dehydrogenase (PQQ-GDH, E.C. 1.1.5.2) as a catalyst, and its substrate D-glucose, the current signal for the trapping adducts from hydroxyl radical was amplified and detected sensitively.…”
Section: Introductionmentioning
confidence: 99%